Communication in corporate social responsibility management - Orjuela Córdoba, Sandra (2011)
The business world is eager for management models that allow being more efficient, surrounded by a development and interest in building a social consciousness. The financial crisis of recent years has led the company to review and be aware of the importance to maintain ethical behavior, to strengthen the management of their own identity from values and from there to manage your image and corporate reputation transparent and reliable.